The Roles of the Fanbase Online Game to the EFL Reading Comprehension Skills - Sandi Nuur Ilma Nabella; Rifki Irawan (FOSTER: Journal of English Language Teaching, 2024)
The proliferation of online games and fanbase communities has created new opportunities for language learning outside traditional classroom settings. Games designed for specific fan communities, such as those centred around K-pop groups, incorporate substantial English language content that may influence English as a Foreign Language (EFL) learners’ reading skills. This study aims to investigate the role of the fanbase online game “BTS Island in the Seom” in developing EFL students’ reading comprehension skills among Indonesian university students. A qualitative case study approach was employed with purposive sampling of five Indonesian university students who had reached level 3000 in the game. Data were collected through semi-structured interviews and document analysis, including academic transcripts and gameplay recordings. Thematic analysis was used to identify patterns and relationships in the data. Four significant roles of the fanbase online game were identified: (1) functioning as an English learning medium that contextualizes language acquisition, (2) facilitating vocabulary enrichment and mastery through repeated exposure, (3) enhancing motivation to engage with English content due to fan interest, and (4) directly improving reading comprehension skills as evidenced by academic performance improvements. Fanbase online games can serve as effective informal learning environments for developing EFL reading comprehension when they successfully integrate engaging content with authentic language use. The strong motivational component derived from fan identity appears particularly significant in sustaining engagement with potentially challenging language content.